The Evergreen : A Northern Seasonal ; Part I.: Spring 1895 ; Part II.: The Book of Autumn 1895 ; Part III.: The Book of Summer 1896 ; Part IV.: The Book of Winter 1896-7. - Geddes, Patrick (Edinburg London Philadelphia : Patrick Geddes and Colleagues T. Fisher Unwin J.B. Lippincott Co., 1895)
Issued in 4 parts: Spring (Volume 1, 1895), Autumn (Volume 2, 1895), Summer (Volume 3, 1896), Winter (Vol. 4, 1896-97). Edited by Patrick Geddes and William Sharp [pseudonym of Fiona MacLeod]. Geddes used The Evergreen to promote his vision of a Celtic Revival amongst Scottish artists and writers. Literary contributors to The Evergreen included Hugo Laubach, Gabriel Setoun, Dorothy Herbertson, Fiona MacLeod, Alexander Carmichael, John Geddie, Margaret Armour, Rosa Mulholland, Noël Paton, George Douglas, William Macdonald, George Eyre-Todd, Nimmo Christie and Paul Desjardins. Artists whose work is illustrated or decorated the pages of The Evergreen included Charles H. Mackie, John Duncan, Helen Hay, Alice Gray, Robert Burns, Paul Serusier, James Cadenhead, Pittendrigh MacGillivray, E.A. Hornel, W.G. Burn Mursdoch, Marion A. Mason, Nellie Baxter, Annie Mackie, Effie Ramsay and Andrew K. Womrath.(https://www.arthistoryresearch.net/review/the-evergreen-a-northern-seasonal.html)
Digitaal ontsloten zie: http://archive.org/details/evergreennorther01gedduoft
Engels
Boek
Keywords: 19de eeuw; literatuur; natuur; seizoenen; poëzie